ChemInform Abstract: A New Reactivity Mode for the Diazo Group: Diastereoselective 1, 3‐Aminoalkylation Reaction of β‐Amino‐α‐Diazoesters to Give Triazolines. Issue 49 (9th December 2014) - Kuznetsov, Alexey; Gulevich, Anton V.; Wink, Donald J.; Gevorgyan, Vladimir
Abstract This method presents a novel mode of reactivity for the diazo group: an intramolecular aminoalkylation of β‐amino‐α‐diazoesters via a 1, 3‐addition of a nucleophile and an electrophile to the diazo group yielding 1, 2, 3‐triazolines.